Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2021
DOI: 10.3390/healthcare9111493
|View full text |Cite
|
Sign up to set email alerts
|

Mindfulness-Based Interventions for Undergraduate Nursing Students in a University Setting: A Narrative Review

Abstract: (1) Introduction: Undergraduate (UG) nursing students are vulnerable to stress throughout their education, known to result in burnout, with high attrition rates of up to 33%. There is a growing body of evidence to suggest that mindfulness-based interventions are effective for the management of anxiety, depression and wellbeing, thereby reducing stress in healthcare provider populations. The aim of this narrative review was to synthesize and provide a critical overview of the current evidence in relation to min… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 73 publications
1
8
0
Order By: Relevance
“…Although so far there has been no research that has revealed the effect of MBSR therapy on anxiety in the population of adolescence scholars who works on undergraduate theses, there are several studies that have found that MBSR group therapy is effective in reducing anxiety levels in scholars majoring in nursing and teacher education (Juul et al, 2021;McVeigh et al, 2021). In a longitudinal study by Dundas, Thorsheim, Hjeltnes and Binder (2016), MBSR therapy was also found to be effective in overcoming scholar's anxiety about academic evaluation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although so far there has been no research that has revealed the effect of MBSR therapy on anxiety in the population of adolescence scholars who works on undergraduate theses, there are several studies that have found that MBSR group therapy is effective in reducing anxiety levels in scholars majoring in nursing and teacher education (Juul et al, 2021;McVeigh et al, 2021). In a longitudinal study by Dundas, Thorsheim, Hjeltnes and Binder (2016), MBSR therapy was also found to be effective in overcoming scholar's anxiety about academic evaluation.…”
Section: Discussionmentioning
confidence: 99%
“…This therapeutic modality was also found to be effective in reducing anxiety levels in college students. (Juul et al, 2021;McVeigh et al, 2021). Then in a longitudinal study by Dundas, Thorsheim, Hjeltnes, and Binder (2016), MBSR therapy was also found to be effective in overcoming students' anxiety about academic evaluation in lectures.…”
Section: Introductionmentioning
confidence: 97%
“…Mindfulness is a psychological process of focusing attention and acceptance on the present. Mindfulness meditation interventions are evidence-based psychoeducation programs (McVeigh et al, 2021). Practitioners are instructed to focus attention on one's breath using simple breathing techniques while simultaneously being aware of any internal and external stimuli (Burger & Lockhart, 2017).…”
Section: Mindfulness Meditationmentioning
confidence: 99%
“…Studies have revealed that nursing students face the same academic concerns as their peers in other disciplines as well as the stress of clinical training (McVeigh et al, 2021). Students in clinical settings often feel they lack knowledge and skills and fear they will make errors and be unable to handle emergency situations (McVeigh et al, 2021). It is important to note that some nursing students actively work in clinical settings where they must contend with the added stress of the coronavirus disease (COVID-19; Edfort & Rux, 2020).…”
mentioning
confidence: 99%
See 1 more Smart Citation